Study of the Effect of 6S Implementation on Hazard in the FKMP UTHM Workshop - LIM YIN, ANASTASIA MEG; ROSLI BIN ASMAWI, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
6S is a practice that is systematically practiced in the implementation of practical work in workshops. The purpose of this study is to evaluate how well 6S students are using practical work in the workshop. This study aims to determine the implementation level, knowledge, understanding, and application of the 6S by FKMP students in the workshop at Universiti Tun Hussein Onn Malaysia's Faculty of Mechanical and Manufacturing Engineering (FKMP). For this investigation, simple random sampling is used. FKMP students who had participated in workshops throughout the course of the semester made up 100 respondents of the sample. A questionnaire with 30 questions was the tool that was employed. In order to determine the reliability of the questionnaire, a pilot test was also carried out. Using the Cronbach Alpha model technique, the reliability of the outcomes of this pilot study is showing a positive value. The statistical analysis was carried out using SPPS (Statistical Product and Service Solutions) version 27. Using descriptive statistics like mean, percentage, and standard deviation, analyse data. The results showed that the 6S practices in term of knowledge, understanding, and application is at high level overall.